Analysis of body composition with bioelectrical impedance analysis in patients with severe COPD and pulmonary emphysema - Rott, Christina; Limen, Eldridge; Kriegsmann, Katharina; Herth, Felix; Brock, Judith (Respiratory medicine, 2024)
Background - Patients with chronic obstructive pulmonary disease (COPD) often suffer from cachexia and malnutrition. Less is known about body composition and nutritional behaviour in patients with advanced COPD and pulmonary emphysema. - Methods - We performed a single-center prospective analysis of patients with COPD GOLD III/IV. Metabolic parameters, dietary and exercise behavior, lung function, exercise capacity and body composition by bioelectrical impedance analysis (BIA) were analyzed. Patients with severe emphysema (emphysema index [EI] >20%) were compared to patients with mild emphysema (EI ≤ 20%). - Results - A total of 121 patients (45.5% female, mean age 64.8 ± 8.1 years, mean FEV1 31.0 ± 8.6%, mean RV 234.7 ± 50.6%) were analyzed, of whom 14.1% were underweight. Only 5% of the patients substituted protein and only about 1/3 performed regular exercise training. BIA showed an unfavourable body composition: body fat ↑, ECM/BCM-index ↑, phase angle ↓ (5.0 ± 0.9°), cell percentage ↓, FFMI (fat-free mass index) ↓. The 94 patients with severe emphysema (mean EI 36.6 ± 8.5%) had lower body-mass-index (22.8 ± 4.3 vs. 31.1 ± 5.8 kg/m2, p < 0.001), FFMI, body weight and body fat, but did not differ significantly in the quality of body composition (e.g. phase angle). Their lipid and glucose metabolism were even better than in mild emphysema patients. - Conclusion - The finding of significantly lower BMI but similar body composition and better metabolic status in severe emphysema patients needs further investigation. However, it should not distract from the necessity to implement dietary and exercise recommendations for advanced COPD patients.